A Review on Energy Efficient Techniques for Wireless Sensor Networks - Mohit Angurala (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Recent advancements have demonstrated that Wireless Sensor Networks (WSNs) that harvest energy from the surrounding environment have the potential to enable continuous network operations using renewable energy sources. However, the spatio-temporal nature of such networks results in significant variations and only allows for intermittent recharging opportunities, leading to minimal data service sustainability. Among the numerous challenges faced by WSNs, energy-aware routing represents a critical constraint that limits the network’s performance. Battery limitations also pose a significant challenge, particularly for battery-powered sensors that consume significant amounts of energy and quickly deplete their battery life. Therefore, this research paper explores various techniques for recharging sensor nodes (SNs) and proposes a robust model that can be utilized in an ad hoc on-demand distance vector routing protocol (AODV) scenario. This model not only improves the energy efficiency of WSNs but also enhances their overall lifespan and reduces traffic congestion.